Trafficking in persons: global patterns - United Nations Office on Drugs and Crime (UNODC) (2006)
Human trafficking is widespread - data taken from the United Nations Office on Drugs and Crime Database on Human Trafficking Trends document the trafficking of human beings from 127 countries to be exploited in 137 countries. Even though all human trafficking cases have their individual characteristics, most follow the same pattern: people are abducted or recruited in the country of origin, transferred through transit regions and then exploited in the destination country. If, at some stage, the exploitation of the victim is interrupted or ended, they can be rescued as victims of trafficking in persons and it is possible they might receive support in the country of destination. Either immediately or at some later point, victims might be repatriated to their origin country; in some cases, relocated in a third country; or, as unfortunately too often still happens, are deported from destination or transit countries as illegal migrants.